Modal preferences in creative problem solving - Deininger, Gina; Loudon, Gareth; Norman, Stefanie (Cognitive processing, 2012)
Embodied cognitive science appeals to the idea that cognition depends on the body as well as on the brain. This study looks at whether we are more likely to engage just the brain or enlist the body for complex cognitive functioning such as creative problem solving. Participants were presented with a puzzle based on De Bono’s lateral thinking puzzles. The puzzle consisted of rotating and joining two-dimensional shapes to make a three-dimensional one. In one condition, participants were given the choice of either solving the puzzle mentally or through manipulation of the images on a computer screen. In another condition, the subjects had to solve the puzzle first mentally and then report which mode they would have preferred to solve the puzzle. Two more conditions were applied with slight variations. In all conditions, an overwhelming majority of participants chose to solve the puzzle by manipulation, even though there was not a significant increase on performance. It appeared that participants were making a conscious choice for the body to play a feedback-driven role in creative cognitive processing. This strong preference for manual manipulation over just mental representation, regardless of the impact on performance, would seem to suggest that it is our natural tendency to involve the body in complex cognitive functioning. This would support the theory that cognition may be more than just a neural process, and that it is a dynamic interplay between body, brain and world. The experiential feedback of the body moving through space and time may be an inherently important factor in creative cognition.